Introduction to global politics [ - Mansbach, Richard W. , 1943-; Taylor, Kirsten L. (London;New York : Routledge, 2008)
Introduces students to the key changes in global politics. This book explains global politics using an historical approach. It helps students to recognize that new developments require citizens to change their beliefs and that new problems may appear even as old ones disappear
Description based on print version record
Includes bibliographical references (p 794-828) and index
Keywords: International relations; International relations -- Forecasting; World politics